Оценка влияния поперечных вихрей на процессы передачи энергии в свободновихревом насосе - Криштоп, И. В.; Герман, В. Ф.; Гусак, А. Г.; Салтанова, Л. М. (НТУ "ХПИ", 2015)
Рассмотрено влияние поперечных вихрей на процесс передачи энергии жидкости в свободновихревом насосе. Представлены напорные и энергетические характеристики этих насосов при различных способах скругления торцов лопастей колеса, полученные экспериментальным путем. Приведены результаты численных исследований течения в межлопастных каналах, которые позволяют уточнить картину течения жидкости в проточной части насоса.

The article describes the influence of transverse vortices on the transfer of the energy of the liquid in a torque flow pump. The head-flow and energetic characteristic curves of these pumps for various ways of rounding the ends of the impeller blades obtained experimentally are presented. A numerical experiment for determining the flow in the channel between the blades was conducted, which allowed to precise the pattern of the flow in the pump.
The influence of transverse vortices on the transfer of the energy in a torque flow pump
Keywords: лопасть; межлопастной канал; численный эксперимент; неравномерность потока; torque flow pump; transverse vortex; channel between the vanes; numerical experiment